Edge effects on small mammals: Differences between arboreal and ground‐dwelling species living near roads in Brazilian fragmented landscapes. (27th October 2017) - da Rosa, Clarissa Alves; Secco, Helio; Carvalho, Nathália; Maia, Ana Carolina; Bager, Alex
Abstract: Habitat fragmentation often induces edge effects that can increase, decrease or have minimal effect upon the population density of a species, depending upon environmental conditions and the requirements of the species. Using a trapping study and generalized linear mixed models, we evaluated edge effects on small tropical mammals living near roads, including two ground‐dwelling ( Akodon sp. and Cerradomys subflavus ) and two arboreal ( Marmosops incanus and Rhipidomys sp.) species. We examined the relationship of these edge effects to environmental factors at both plot and patch scales. Generalist ground‐dwelling species were attracted to edges, with higher population densities recorded in habitats close to road or matrix edges where vegetation density was lower. In contrast, populations of the generalist arboreal species avoided edge habitats, their populations were found in greater density in habitats far from roads/matrix edges. Thus, our results show that patterns of edge habitat utilization were related to the ecological requirements of each species. These findings are especially important in the tropics, where demand for economic growth in many countries has accelerated the fragmentation process and has recently culminated in increased road construction and expansion. Fragmented habitats promote an increase in edge environments, and consequently will reduce the abundance of arboreal small mammal species, such as those used as models in this study.